Water Uptake and Germination of Corn Grains in Different Solutions - JAGDEV S.; OMAR, M. R. (The Libyan Journal of Agriculture, 2023)
Corn grain of the open pollinated ‘American Early’ variety was placed on blotters moistened with different concentrations of hydrogen peroxide, thiourea and potassium nitrate for 42 hours until the radicle emerged in a 25°C temperature controlled germina-tor. The increase in weight of the grain was recorded after 6,18 and 42 hours. The data on percent germination and radicle and plumule lengths were recorded at the end of the experiment. In all the three chemicals, the three phases of water absorption were observed.